О проблемах государственного контроля органов исполнительной власти в Российской Федерации - Гриценко, Валентина Васильевна; Гриценко, Валентина Василівна; Gricenko, Valentina (My University, 2013)
This article examines the key issues of the implementation of the executive authorities of the Russian Federation government control in light of the administrative reform. Justified by the need to create a single codified act that would regulate relations of financial control.
Гриценко В. В. О проблемах государственного контроля органов исполнительной власти в Российской Федерации / В. В. Гриценко // Наукові праці Національного університету «Одеська юридична академія» : зб. наук. пр. / редкол.: С. В. Ківалов (голов. ред.), В. М. Дрьомін (заст. голов. ред.), Ю. П. Аленін [та ін.] ; відпов. за вип. В. М. Дрьомін ; МОН України, НУ ОЮА. – Одеса : Юрид. л-ра, 2013. – Т. 13. – С. 238-251.
Keywords: контроль; государственный контроль; финансовый контроль; органы исполнительной власти; державний контроль; фінансовий контроль; органи виконавчої влади; control; financial control; executive agencies